Dinamika Tes Peringkat Hafalan - Aisyah Nur Amalia (Fakultas Ushuluddin dan Dakwah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2019)
In addition to the book base, memorization of the Qur'an is also the main base of various Islamic boarding schools in this archipelago. With techniques and methods that have been widely used, one of the typical traditions of rote evaluation carried out by the An-Nur Ngrukem Islamic boarding school is the memorization ranking test. In practice, the memorize ranking tests have various dynamics experienced by female students. This article explains how the dynamics of female students encounter memorized ranking test related to the study of Quran living at the An-Nur Ngrukem Islamic Boarding School. The case study research that forms the basis of this paper, proves the existence of internal and external factors in the dynamics of female students in the face of memorization ranking tests. Among them, internal factors; puberty, mental readiness, tenacity and memorization, and patience. While external factors; need some tips from dzuriyyah and administrators, the strict requirements and conditions of the test, the increasing number of students at the An-Nur Ngrukem Islamic Boarding School and need to manage the time.